2014
DOI: 10.1177/0193945914537123
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Depressive Symptoms in Four Ethnic Groups of Midlife Women

Abstract: The purpose of this study was to determine the associations between physical activity and depression and the multiple contextual factors influencing these associations in four major ethnic-groups of midlife women in the U.S. This was a secondary analysis of the data from 542 midlife women. The instruments included questions on background characteristics and health and menopausal status; the Depression Index for Midlife Women; and the Kaiser Physical Activity Survey. The data were analyzed using chi-square test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Findings from our study also indicated that lack of regular exercise was an independent factor of increased risk for depressive symptoms in late middle-aged women. This result is consistent with previous research that depressive symptoms were negatively correlated with physical activity in women [ 42 ] and that regular physical activity reduced depressive symptoms, most notably among mildly depressed women [ 43 ]. A Cochrane review, based on 35 randomized controlled trials, also concluded that exercise was moderately more effective than a control intervention for reducing symptoms of depression [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Findings from our study also indicated that lack of regular exercise was an independent factor of increased risk for depressive symptoms in late middle-aged women. This result is consistent with previous research that depressive symptoms were negatively correlated with physical activity in women [ 42 ] and that regular physical activity reduced depressive symptoms, most notably among mildly depressed women [ 43 ]. A Cochrane review, based on 35 randomized controlled trials, also concluded that exercise was moderately more effective than a control intervention for reducing symptoms of depression [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Looking at the two findings vis-à-vis each other, less participation in positive health practices is an outcome of depressive symptoms as proposed theoretically (Atkins, 2010; Bandura, 2004; Billingsley & Billingsley, 1987). The current findings support those of prior studies that tested this relationship utilizing psychometrically sound scales that measure a variety of health practices (Lindgren, 2001, 2003; Zauszniewski et al, 2001) and those that measured one specific health practice (Im et al, 2015; Walsh et al, 2013) in women. The current findings add to the knowledge base regarding the relationship between depressive symptoms and positive health practices in Black single mothers.…”
Section: Discussionsupporting
confidence: 83%
“…Depressive symptoms were positively associated with health compromising behaviors such as smoking, binge drinking, risky sexual behaviors, physical inactivity, poor diet, and lack of sleep ( B = .12–.20, p < .01) in a sample of multiethnic low-income adults (47% female, 68% African American; Walsh, Senn, & Carey, 2013), and a negative relationship between depressive symptoms and physical activity ( r = −.18, p < .01) was found in a multiethnic sample of 542 midlife women (Im, Ham, Chee, & Chee, 2015). The severity of depressive symptoms was associated with increased prevalence of risk behaviors, such as smoking, physical inactivity, and obesity among 18,856 persons with asthma (Strine et al, 2008).…”
Section: Theoretical Model Of Outcomes Of Depressionmentioning
confidence: 97%
“…For example, a cross‐sectional and prospective‐longitudinal epidemiological study in Germany found that regular physical activity was associated with beneficial effects on mental health (Ströhle et al, ). Regarding the association between MDD and physical activity, there is empirical evidence showing that the risk for depression is significantly higher in physically inactive as compared to physically active individuals (e.g., Im, Ham, Chee, & Chee, ; McKercher et al, ; Weyerer, ). To illustrate, results of the Aerobics Center Longitudinal Study by Galper, Trivedi, Barlow, Dunn, and Kampert (), a national cohort study of 5,451 men and 1,277 women (age: 20–88) across the United States, found that physically inactive men and women were found to be more severely depressed than their active counterparts.…”
Section: Introductionmentioning
confidence: 99%